Genetic variation in the TNF receptor-associated factor 6 gene is associated with susceptibility to sepsis-induced acute lung injury - Song, Zhenju; Yao, Chenling; Yin, Jun; Tong, Chaoyang; Zhu, Duming; Sun, Zhan; Jiang, Jinjun; Shao, Mian; Zhang, Yaping; Deng, Zhi; Tao, Zhengang; Sun, Si; et al. (Journal of translational medicine, 2012)
Background Recent studies showed that overwhelming inflammatory response mediated by the toll-like receptor (TLR)-related pathway was important in the development of acute lung injury (ALI). The aim of this study was to determine whether common genetic variation in four genes of the TLR signaling pathway were associated with sepsis-induced ALI susceptibility and risk of death in Chinese Han population. Methods Fourteen tag single nucleotide polymorphisms (tagSNPs) in MyD88 , IRAK1 , IRAK4 and TRAF6 were genotyped in samples of sepsis-induced ALI (n = 272) and sepsis alone patients (n = 276), and tested for association in this case-control collection. Then, we investigated correlation between the associated SNP and the mRNA expression level of the corresponding gene. And we also investigated correlation between the associated SNP and tumor necrosis factor alpha (TNF-α) as well as interleukin-6 (IL-6) concentrations in peripheral blood mononuclear cells (PBMCs) exposed to lipopolysaccharides (LPS) ex vivo . The mRNA expression level was determined using real-time quantitative Polymerase Chain Reaction (PCR) assays, and concentrations of TNF-α and IL-6 were measured by enzyme-linked immunosorbent assay (ELISA). Results The association analysis revealed that rs4755453, an intronic SNP of TRAF6 , was significantly associated with susceptibility to sepsis-induced ALI. The C allele frequency of rs4755453 in the sepsis alone group was significantly higher than that in the sepsis-induced ALI group ( P = 0.00026, odds ratio (OR) = 0.52, 95% confidence interval (CI) 0.37–0.74). These associations remained significant after adjustment for covariates in multiple logistic regression analysis and for multiple comparisons. TRAF6 mRNA expression levels in PBMCs from homozygotes of the rs4755453G allele were significantly higher than that in heterozygotes and homozygotes of the rs4755453C allele at baseline ( P = 0.012 and P = 0.003, respectively) as well as after LPS stimulation ( P = 0.009 and P = 0.005). Moreover, the concentrations of TNF-α and IL-6 in cell culture supernatants were also significantly higher in the subjects with rs4755453GG genotype than in subjects with CG and CC genotype. None of the 14 tagSNPs showed associations with risk of death and severity among ALI cases. Conclusions Our findings indicated that common genetic variants in TRAF6 were significantly associated with susceptibility to sepsis-induced ALI in Chinese Han population. This was the first genetic evidence supporting a role for TRAF6 in ALI.